Perspectives from Maghreb States Regarding Import and Export of Food Products - Tomé, Beatriz (UNISCI Discussion Papers, 2014)
This article tries to complement the views offered by other authors in this volume with the proviso that my point of departure stands on the Maghreb perspective regarding the agricultural trade with the European Union (EU). I argue that these particular trade relations constitute a key element in the extensive and plural Euro-Maghreb network and that they influence not only the external relations of Morocco, Tunisia and Algeria, but also their internal ones. The agro-trade reflects the mutual and contant influences among the international level (level of analysis I) and the domestic one (level os analysis II). In this paper I seek to explore how the agreements between the EU and the Mediterranean Thrid Countries (MTC) do reflect not only European expectations, but also the interests and agendas of the Maghreb States.